URGENSI DAN PENGARUH INOVASI PRODUK TERHADAP MINAT BELI PADA KUE NENEK MOYANG PEMATANG SIANTAR - Julyanthry Julyanthry; Marto Silalahi; Hendrick Sasimtan Putra; Debi Eka Putri; Annisa Hamzah (Universitas Mahendradatta Denpasar, 2024)
Abstract - This study aims to examine and understand the influence of product innovation on purchase intention at Kue Nenek Moyang in Pematang Siantar. The approach used includes literature and field research, with 55 consumers as the sample. The data used in this study are qualitative and quantitative, sourced from primary and secondary data. Data collection was carried out through questionnaires, interviews, documentation, and observations. Validity and reliability tests were applied to the research instruments, and data were analyzed using normality tests and qualitative and quantitative descriptive analyses. The study results indicate that: 1) product innovation and consumer purchase intention are considered good; 2) there is a positive influence of product innovation on purchase intention; 3) there is a strong relationship between product innovation and purchase intention, where the level of purchase intention is influenced by product innovation; 4) the hypothesis test shows that H0 is rejected, confirming a positive and significant influence of product innovation on purchase intention at Kue Nenek Moyang in Pematang Siantar.